Using stakeholder feedback to improve online professional development opportunities. Issue 2 (2nd April 2020) - Nese, Rhonda N. T.; Meng, Paul; Breiner, Sarah; Chaparro, Erin; Algozzine, Robert
Abstract: Traditional professional development is often characterized as being expensive, time consuming, and lacking impact. In contrast, online professional development provides greater flexibility and is becoming increasingly popular for school personnel. In this article, we report the process and outcomes of gathering feedback to adapt traditional in-person to online training differentiated for the participants to maximize utility, efficiency, and effectiveness in meeting the needs of key stakeholders. Focus groups were conducted with teachers, administrators, and other specialists to gather feedback on content as well as how online learning modules (OLMs) could be tailored to meet specific school site and team needs. We discuss our findings in the context of continuing efforts to improve general and specific professional development opportunities.